Quality control index survey for railway bridge health monitoring - Lajevardi, Sadegh (2019)
Inspection and rehabilitation are the most important activities during any maintenance procedure. A maintenance project demands to manage resources with regard to data related to components’ condition, defined by a given index. In this manner, data sets obtained for each index, and for each case study, are used for finding the new quality control index with maximum value of data. In this approach, risk analysis is used for prioritization and reducing costs with increasing data value with focusing on important elements as well as maximizing value of information (VoI) in measurements and inspections. Risk analysis is the most common tool for data mining and intelligent judgment obtained from observations. Risk analysis results are usually calculated to find the weight for each data set index in terms of their scores, which are called factor scores and finding the new quality control indexed for each case. Finally, the major and important index according to their weight and risk scores, is obtained and used for decision making in maintenance projects. An application is shown consisting of 29 Railway Bridges in suburban area with data obtained from periodic inspections. All of these bridges are constructed in reinforced concrete. Finally, it is desirable to produce new check list with regard to important data and quality control indexes. The priority of each bridge in the railway network as well as the priority for each component in their structure could be obtained by the new quality control indexes. Resource planning usage for the network component could be determined by this approach after computation of the new quality control index. Resources planning consists of inspection intervals and their materials usage for maintenance activities.